Preferential Liberalization, Antidumping, and Safeguards : Stumbling Block Evidence from MERCOSUR - Bown, Chad P. (World Bank, Washington, DC, 2016)
There is not yet consensus in the trade agreements literature as to whether preferential liberalization leads to more or less multilateral liberalization. However, research thus far has focused mostly on tariff measures of import protection. This paper develops more comprehensive measures of trade policy that include the temporary trade barrier policies of antidumping and safeguards. Studies in other contexts have also shown how these policies can erode some of the trade liberalization gains that arise when examining tariffs alone. This paper examines the experiences of Argentina and Brazil during the formation of the MERCOSUR over 1990-2001. The study finds that an exclusive focus on applied tariffs may lead to a mischaracterization of the relationship between preferential liberalization and liberalization toward non-member countries. First, any "building block" evidence that arises by focusing on tariffs during the period in which MERCOSUR was only a free trade area can disappear, once the analysis includes changes in import protection arise through temporary trade barriers. Furthermore, there is also evidence of a "stumbling block" effect of preferential tariff liberalization for the period in which MERCOSUR became a customs union, and this result tends to strengthen with the inclusion of temporary trade barriers. Finally, the paper provides a first empirical examination of whether market power motives can help explain the patterns of changes in import protection that are observed in these settings.